Contemporary Ijtihad by Muhammadiyah on the Dawn (Fajr) Time Controversy: Analysis of Maqāṣid al-Sharī'ah and the Response of the Muhammadiyah Mosque Prosperity Council in Makassar City - Alamsyah; Salam, Hisbullah; Masuwd, Mowafg Abrahem (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2025)
Muhammadiyah's determination of Fajr prayer time using a sun angle of -18° has elicited varied responses from the community. This study aims to analyze Muhammadiyah’s scientific approach and the accompanying social dynamics. The research employed a qualitative case-study method, involving literature studies, field observations, and semi-structured interviews with religious leaders and congregants at Muhammadiyah mosques in Makassar City. Key findings indicate that 76.19% of Muhammadiyah Mosque Prosperity Council (DKM) members accept the Muhammadiyah Central Board’s criteria for determining Fajr time; however, only 66.67% have implemented these criteria. This moderate implementation rate reflects a significant gap between theoretical acceptance and practical application, indicating issues of community readiness and internal communication effectiveness. Supporting factors for implementation include the availability of recent astronomical data, Muhammadiyah's spirit of tajdīd (renewal), and the integrity of falak (Islamic astronomy) methodology. Conversely, limiting factors include low public literacy, insufficient socialization at mosque-level, and congregants’ apprehension about change due to unfamiliarity with the revised criteria. Analysis based on maqāṣid al-sharī'ah is relevant in this context. Principles such as ḥifẓ al-dīn (preserving religion), ḥifẓ al-nafs (maintaining inner peace), and ḥifẓ al-‘aql (maintaining rationality) are essential considerations in contemporary ijtihad. This approach ensures that religious renewal, including the revision of Fajr prayer time, is valid in terms of Islamic law, ethical, educational, and socially acceptable. The implication of this study is the necessity to integrate astronomical aspects with strategic socialization and educational programs to enable rational acceptance of Islamic legal transformations and reduce community resistance effectively.